Analysis of Causes of Piping Welding Defects in Steam Gas Power Plants with FMEA and AHP method - Horas Canman; Hasbullah Hasbullah (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
High welding intensity is an integral part of the construction process of a Steam Gas Power Plant (PLTGU). The existence of weld defects has a significant potential for rework, additional construction costs, and delays in project completion. In the fabrication of pipe joints by welding in the PLTGU additional construction project with a capacity of 650 MW in Muara Tawar, welded joints were found to be rejected at 22.44%. This study aimed to analyze and determine the leading causes of rejected weld defects at the welded joint using the methods used, namely FMEA and AHP. Based on the Pareto diagram, it is known that two types of welding defects dominantly occur in welded joints which will then become the priority for repairs carried out by the contractor, namely porosity and cluster porosity. Based on the FMEA method, it is known that two groups of Risk Priority Number (RPN) values differ quite a lot, namely the group with low RPN values (1-140) and the group.